Innovation in Curriculum Management Based on the Integration of Islamic Values to Improving the Quality of Education at Junior High School - Adriana; Usfandi Haryaka; Masrur; Nurlaili; Widyatmike Gede Mulawarman; Azainil (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to examine the management of an Islamic value–integrated curriculum at SMP Islam Bunga Bangsa Samarinda and its contribution to improving educational quality by balancing academic achievement, character formation, and spiritual development. A qualitative descriptive method was used, employing interviews, observations, and document analysis involving school leaders, teachers, and curriculum teams, with data analyzed through thematic analysis and triangulation. The findings show that Islamic-integrated curriculum management is implemented systematically through planning, organizing, implementation, evaluation, and effectiveness stages, aligning the Merdeka Curriculum and National Education Standards with Islamic character education across subjects. The study is applicable to Islamic schools, curriculum development, and educational management practices, offering guidance for school leaders and policymakers. Its originality lies in presenting a practical and structured model of curriculum management that integrates Islamic values within a national curriculum framework to enhance educational quality.